2000
DOI: 10.1080/13556210050003711
|View full text |Cite
|
Sign up to set email alerts
|

Screening for fetal alcohol syndrome: is it feasible and necessary?

Abstract: The potential to utilize screening strategies to improve the identification and outcome of persons with fetal alcohol syndrome (FAS) is reviewed. FAS is a condition where screening and surveillance activities would be appropriate. Development of FAS screening and surveillance programs is encouraged because the disorder is expensive. People with FAS have poor outcomes as adults with less than 10% living independently. Several useful tools and models are available. Screening would improve ascertainment and preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Screening high-risk individuals for FASD, such as children in the child welfare, criminal justice, and special education systems, would increase the number of individuals who are recognized and diagnosed. Several studies documenting higher rates of FASD in these systems have demonstrated screening can be effectively implemented [34-36]. Once diagnosed, families need to be able to qualify for and access appropriate services for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Screening high-risk individuals for FASD, such as children in the child welfare, criminal justice, and special education systems, would increase the number of individuals who are recognized and diagnosed. Several studies documenting higher rates of FASD in these systems have demonstrated screening can be effectively implemented [34-36]. Once diagnosed, families need to be able to qualify for and access appropriate services for their children.…”
Section: Discussionmentioning
confidence: 99%
“…A second and equally problematic area is in the diagnosis of FASD. The lack of routine population or clinic‐based screening efforts results in under referral of high‐risk infants and children for evaluation (Burd et al . 2000).…”
mentioning
confidence: 99%
“…In previous publications we have articulated the need for multiple screening efforts in a variety of settings. 8,14,15 In Figure 1 we depict a screening process that has the following features: 1) it is brief; 2) the steps are incremental and more time and effort are required as the risk for an adverse outcome increases; 3) the process builds on previous data collected in the chart; and 4) it ends with intervention recommendations based on a comprehensive data set that allows for risk-based intervention and ongoing follow-up that does not require that all screening steps be repeated.…”
Section: Rationale For a Staged Screening Processmentioning
confidence: 99%